Pengaruh Bauran Pemasaran Tabungan Haji Terhadap Tingkat Kepuasan Nasabah Di Bank BNI Syariah Kantor Cabang Pembantu Kota Pagar Alam - Reynita Anugrah Putri; Dismita Citra Dewi; M Agus Maryanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2019)
This study aims to determine the effect of marketing mix variables consisting of products, prices, promotions and places on customer satisfaction at BNI Syariah KCP Pagar Alam. The model used in this study is the method of observation, interviews, questionnaires, and literature study using a Likert scale and determination of the sample using the Slovin formula using 58 samples. Data analysis method used is multiple linear regression method. The results showed that the marketing mix consisting of Product (X1), Price (X2), Promotion (X3), and Place (X4), together had a positive and significant effect on customer satisfaction. Where the multiple linear regression equation is Y = 2.086 + 0.313 X1 + 0.322 X2 + 0.135 X3 + 0.362 X4. In addition, the F test shows that the marketing mix has a significant effect on customer satisfaction with a significance level of 0,000. However, based on the t-test, the variables that significantly influence customer satisfaction are the Product variable with a value of 0.001, Price of 0.011, Place of 0.002 and the Promotion variable does not have a significant effect on customer satisfaction with a significant level of 0.224.